Retrospective analysis of inflammatory biomarkers and prognosis in non-small cell lung cancer without adenocarcinoma in situ - Zhao, Qing; Cui, Songping; Hu, Bin; Chen, Shuo (Frontiers in Genetics, 2025)
BackgroundInflammatory biomarkers have shown prognostic value in Non-Small Cell Lung Cancer (NSCLC), but the inclusion of Adenocarcinoma In Situ (AIS) cases in previous studies may introduce bias. This study aims to evaluate the prognostic significance of inflammatory biomarkers in NSCLC while excluding AIS.MethodsThis study included patients who received surgery for lung carcinoma from August 2016 and August 2019. We collected demographic, clinical, laboratory, and outcome information. Inflammatory biomarkers were analyzed using receiver operating characteristic (ROC) curves, Kaplan-Meier survival analysis, and Cox regression to assess their prognostic value.ResultsHigher levels of inflammatory biomarkers correlated with poorer survival, with significant differences in overall survival (OS) between high- and low-expression groups. However, multivariate Cox regression identified age, tumor stage, and differentiation as independent prognostic factors, while biomarkers were not independently predictive.ConclusionInflammatory biomarkers have short-term prognostic value in invasive NSCLC, but traditional clinical and pathological factors remain key for long-term outcomes.